Pola Pemberatan Pidana dalam Hukum Pidana Khusus - RAHARJO, FAJAR; YUDHAYANA, ADHI; PRATIWI, INDAH; RIO FERDIAN, MUHAMMAD BAGAS; PUTRA, TEGAR HARBRIYANA (Muhammadiyah Law Review Journal, 2025)
What has been a fundamental issue of this study what base for the lawgivers in determining â€œtype andÂ numberâ€ of crime showing a disapprobation. Is there any certain pattern used by the lawgivers in determiningÂ theÂ caseÂ inÂ SpecialÂ CriminalÂ Code,Â primarilyÂ toÂ doÂ itsÂ weightingÂ whenÂ comparedÂ withÂ theÂ general pattern used in the Criminal Code. This research was conducted by using a normative juridicalÂ method,Â mainlyÂ byÂ analyzingÂ theÂ symptomsÂ suggestedÂ byÂ theÂ legislatorsÂ inÂ theÂ enactmentÂ ofÂ criminal threats.Â TheÂ resultsÂ ofÂ thisÂ studyÂ indicateÂ thatÂ inÂ theÂ SpecialÂ CriminalÂ Law,Â becomingÂ theÂ â€œsymbolâ€Â of Criminal Law as the identity of Indonesia, there is no specific pattern in conducting the weighting ofÂ criminal.Â KeyÂ wordsÂ :Â CriminalÂ weighting,Â theÂ specialÂ criminalÂ law,Â criminal.